RECONCEIVING CONSTRUCTION IN THE CONTEXT OF HUMANISATION - Philip McAleenan; Ciaran McAleenan (Journal of Construction Project Management and Innovation)
Construction, like agriculture, is potentially the most humanising of all activities, in that it has the potential to satisfy or contribute to the satisfaction of the fundamentals outlined in Maslow’s hierarchy of needs. More than this, construction has the capacity to reflect and contribute to the assertion of “being”, the ongoing struggle to define and assert our authentic self. Conversely, in both process and outcome, it also has the potential to dehumanise and to negate ontological potential. This paper examines the ethical and moral challenges arising from the societal responsibilities required of and inherent in the construction industry’s raison d’être. Through an examination of the literature and of selected projects, the contribution to and the negation of an authentic ethic is explored, challenging stakeholders to evaluate the positive and address the negative in such a way that construction meets its obligations to society and to individuals. Within the context of humanisation, the objective is the development of a model for construction that promotes respect for all and accords equal consideration of all and to all.